Improving Patient Experience by Teaching Empathic Touch and Eye Gaze: A Randomized Controlled Trial of Medical Students. (December 2020) - Lecat, Paul; Dhawan, Naveen; Hartung, Paul J; Gerzina, Holly; Larson, Robert; Konen-Butler, Cassandra
Background: Empathy is critical for optimal patient experience with health-care providers. Verbal empathy is routinely taught to medical students, but nonverbal empathy, including touch, less so. Our objective was to determine whether instruction encouraging empathic touch and eye gaze at exit can impact behaviors and change patient-perceived empathy. Materials: A randomized, controlled, double-blinded trial of 34 first-year medical students was conducted during standardized patient (SP) interviews. A video either encouraging empathic touch and eye gaze at exit or demonstrating proper hand hygiene (control) was shown. Encounter videos were analyzed for touch and eye gaze at exit. The Jefferson Scale of Patient Perceptions of Physician Empathy was used to measure correlations. Intervention students were surveyed regarding patient touch. Results: Of this, 23.5% of intervention students touched the SP versus zero controls; 88.2% of intervention students demonstrated eye gaze at exit. Eye gaze at exit positively impacted patient-perceived empathy (correlation = 0.48, P > .001). Survey responses revealed specific barriers to touch. Conclusion: Medical students may increase perceived empathy using eye gaze at exit. Instruction on empathic touch and sustained eye gaze at exit at the medical school level may be useful in promoting empathic nonverbal communication. Medical educators should consider providing specific instructions on how to appropriately touch patients during history-taking. This is one of the few studies to explore touch with patients and the first ever to report the positive correlation of a health provider's sustained eye gaze at exit with the patient's perceived empathy. Further studies are needed to explore barriers to empathic touch.